The Effects of L-carnitine in Reducing Hepatotoxicity of Statins in Rats - K. Ibrahim, Doaa; A. Bader, Shahad; Bader, O. A. (Medicinski časopis, 2024)
The first line of treatment for hyperlipidemia is statins. Of this group, atorvastatin is the most popular and effective drug. Hepatic toxicity and myopathy are the two observed adverse effects of statins. The active form of carnitine is L-carnitine, a water-soluble compound found in food, the body, and the majority of dietary supplements. There are many uses for L-carnitine in the human body. It assists in the removal of free radicals from the body and lowers hydrogen peroxide production, both of which may guard against liver side effects brought on by statins. The eighty rats were randomly divided into four main groups: control, L-carnitine, atorvastatin, and combination (L-carnitine + atorvastatin) groups. These groups were subdivided into three subgroups based on different doses of the drugs. The L-carnitine group was divided into L200, L300, and L400. The atorvastatin group was divided into A10, A15, and A20. The combination group was subdivided into AL10/200, AL15/300, and AL20/400. All groups received their treatments daily for one month. According to our findings, the effects of L-carnitine (200 mg/kg daily) on the increase in AST brought on by atorvastatin are not statistically significant, although they are significant on the increases in ALT, ALP and TSB. L-carnitine still has substantial impacts on ALT, ALP and TSB even at larger doses, while its impacts on AST levels had become significant.
Keywords: L-carnitine; Atorvastatin; Liver enzymes; Liver injury